(untitled) (Eurasian Journal of Ecology, 2016)
The results of breeding work on creation of high-yielding, short-stalk varieties of soft wheat of Kazakhstan selection of intensive type. Were used signs of “genes” dwarfing (rht1, rht2,rht3) varieties of Krasnodar and Ukrainian selection: Bezostaya and their mutants, Dwarf 1, Progress, etc. On the basis of these genes-source varieties, method of беккросс were created high-yielding, short varieties of soft wheat: Almaly, Arap, Myra and alia.